VAR ANALYSIS: ASSOCIATION BETWEEN NON-PERFORMING LOAN, HOUSING PRICE, ECONOMIC INDICATORS, AND MORTGAGE - Gultom, Yulifar Amin; Muchtar, Masruri; Sihombing, Pardomuan Robinson (Jurnal Akuntansi dan Keuangan Indonesia, 2025)
Background: The economic crisis from 2008 to 2009 was due to the collapse of the housing price bubble, which increased the default rate or non-performing loans of mortgages. Much research on non-performing loans compared to property price and economic indicators has been done in other countries, but not in Indonesia. This research is modified to suit the housing market in Indonesia, aiming to investigate causality relationships between non-performing loans, residential property price index, gross domestic product, mortgages, and credit interest rates. It also analyzes the impulse response function and variance decomposition of each variable, focusing on non-performing loans to show the effect of shocks from other variables. Methods: The study uses a vector autoregression model. Findings: The result shows that there are causality relationships between non-performing loans, residential property price index, gross domestic product, mortgages, and credit interest rates. Furthermore, compared to the normal period, in a crisis period, no specific trend is found from the decomposition of all variables to the non-performing loans. Conclusion: This research also shows that monetary and fiscal policies from the government can affect non-performing loans and mortgages. The increase in house prices by the property firm must be applied carefully to avoid a negative effect on the economy. Novelty/Originality of this article: This research is specifically adapted to the housing market in Indonesia, addressing a gap in previous studies. It also provides detailed analysis of impulse response function and variance decomposition focused on non-performing loans.